2017
DOI: 10.1002/pro.3137
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule force spectroscopy reveals the effect of BiP chaperone on protein folding

Abstract: BiP (Immunoglobulin Binding Protein) is a member of the Hsp70 chaperones that participates in protein folding in the endoplasmic reticulum. The function of BiP relies on cycles of ATP hydrolysis driving the binding and release of its substrate proteins. It still remains unknown how BiP affects the protein folding pathway and there has been no direct demonstration showing which folding state of the substrate protein is bound by BiP, as previous work has used only peptides. Here, we employ optical tweezers for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 32 publications
5
39
1
Order By: Relevance
“…Recently, our group has been studying BiP binding properties, unfolding completely a protein substrate using single molecule optical tweezers. Our results showed that BiP binds to the unfolded state of MJ0366 substrate protein reversibly, preventing its refolding, and that this effect depends on both the type and concentration of nucleotides …”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Recently, our group has been studying BiP binding properties, unfolding completely a protein substrate using single molecule optical tweezers. Our results showed that BiP binds to the unfolded state of MJ0366 substrate protein reversibly, preventing its refolding, and that this effect depends on both the type and concentration of nucleotides …”
Section: Introductionmentioning
confidence: 68%
“…Another interesting point to note is the allosteric communication between both BiP structural domains, which it has been described as an important feature that modulates BiP functionality. 3,6 In our group we have studied allosterism in both directions: first, from the NBD to the SBD, 15 studying BiP mechanical properties at the single molecule level with optical tweezer manipulation, and now in this work from the SBD to the NBD with ensemble measurements with nano-rheological experimental setup. This study has shown that there exists a communication between both domains, as when peptide is bound in the SBD, the affinity for ADP bound in the NBD is modified (evidenced by the drop in K D value), demonstrating that SBD is allosterically coupled to NBD, as described in previous studies.…”
Section: K D 'S Determination For Bip Nucleotides and Allosterism Betmentioning
confidence: 99%
See 3 more Smart Citations